2013
DOI: 10.1371/journal.pone.0076103
|View full text |Cite
|
Sign up to set email alerts
|

The Graft of Autologous Adipose-Derived Stem Cells in the Corneal Stromal after Mechanic Damage

Abstract: This study was designed to explore the feasibility of using autologous rabbit adipose derived stem cells (rASCs) as seed cells and polylactic-co-glycolic acid (PLGA) as a scaffold for repairing corneal stromal defects. rASCs isolated from rabbit nape adipose tissue were expanded and seeded on a PLGA scaffold to fabricate cell-scaffold constructs. After 1 week of cultivation in vitro, the cell-scaffold complexes were transplanted into corneal stromal defects in rabbits. In vivo, the autologous rASCs-PLGA constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…When these cells were injected into wounded corneas, these cells prevented fibrotic scar formation and contributed to the regeneration of stromal ECM with lamellar structure and collagen organization typical for normal corneas (Basu et al, 2014). Overall, these studies open up new avenues for fibrosis treatment with a possibility for using autologous sources, such as limbal biopsies or adipose derived stem cells (Ma et al, 2013). …”
Section: Corneal Stromal Wound Healingmentioning
confidence: 99%
“…When these cells were injected into wounded corneas, these cells prevented fibrotic scar formation and contributed to the regeneration of stromal ECM with lamellar structure and collagen organization typical for normal corneas (Basu et al, 2014). Overall, these studies open up new avenues for fibrosis treatment with a possibility for using autologous sources, such as limbal biopsies or adipose derived stem cells (Ma et al, 2013). …”
Section: Corneal Stromal Wound Healingmentioning
confidence: 99%
“…The majority of studies have been performed using MSC derived from either bone marrow (13 studies) [13, 14, 17, 22–24, 38–40, 43, 47, 48, 50] or adipose tissue (9 studies) [19, 33, 35, 42, 44–46, 49, 51], with the remainder using MSC extracted from either umbilical cord tissues (4 studies) or dental pulp (2 studies) . Most studies have used cultures of MSC established from human tissues (19 studies) [13, 18–20, 23, 24, 33–39, 41, 42, 45, 46, 49, 51], with the balance having been established from rabbits (5 studies) , rats (3 studies) , and mice (1 study) .…”
Section: Overview Of Published Literaturementioning
confidence: 99%
“…The majority of studies have been performed using MSC derived from either bone marrow (13 studies) [13, 14, 17, 22-24, 38-40, 43, 47, 48, 50] or adipose tissue (9 studies) [19, 33, 35, 42, 44-46, 49, 51], with the remainder using MSC extracted from either umbilical cord tissues (4 studies) [20,34,36,41] or dental pulp (2 studies) [18,37]. Most studies have used cultures of MSC established from human tissues (19 studies) [13, 18-20, 23, 24, 33-39, 41, 42, 45, 46, 49, 51], with the balance having been established from rabbits (5 studies) [14,17,43,44,48], rats (3 studies) [40,47,50], and mice (1 study) [22]. A large proportion of studies (19 studies) [13, 14, 17, 18, 20, 22, 24, 33-35, 37, 38, 40, 42-44, 47-49] have involved in vivo experiments, with 11 studies involving administration of human MSC into rabbits (6 studies) [18,33,35,37,38,42], rats (3 studies) [13,24,49], or mice (2 studies) [20,34].…”
Section: Overview Of Published Literaturementioning
confidence: 99%
“…rbASCs have been used in tissue regeneration models for bone, cartilage, and cornea, but it has not been explicitly demonstrated that these stem cells are multipotent (Bahrani et al, ; De Girolamo et al, ; Ma, Bao, Cui, & Zou, ). Our results show that, like rat and human ASCs (Gimble, Katz, & Bunnell, ; Zuk, ), rbASCs are multipotent and are able to differentiate along chondrogenic, osteogenic, and adipogenic lineages.…”
Section: Discussionmentioning
confidence: 99%